Ensaios pré-clínicos e clínicos com óleo essencial de Cymbopogon citratus (DC) Stapf. para tratamento de pitiríase versicolor. - Carmo, Egberto Santos (2011)
The aim of this study was to evaluate the antifungal potential of essential oil of Cymbopogon citratus (DC) Stapf. against Malassezia spp. We determined the minimum inhibitory concentration-MIC of essential oil of C. citratus on different strains of Malassezia, possible mechanisms of action by the writings of ergosterol (50-250 mg/mL) and sorbitol (0.8 M), and acute toxicity tests in mice (2000 mg/kg orally) and skin irritation in rabbits (application of essential oil in MIC90). After the pre-clinical tests were carried out clinical trials of phase I and II with shampoo, creamy lotion containing essential oil of C. citratus, respectively, in subjects healthy and with pityriasis versicolor. There was this work that the pityriasis versicolor reaches men and women alike, regardless of color and age, and the region of the posterior and anterior trunk the most affected. And the fungal species most frequently isolated were M. sympodialis and M. furfur. In preclinical evaluation in vitro antifungal activity of essential oil of C. citratus there was an MIC90 of 1.25 μL/mL. With the addition of ergosterol, the MIC increased about fourfold, suggesting a possible action of this oil on the fungal membrane. In pre-clinical toxicity in vivo was found low toxicity of essential oil of C. citratus, especially at 1.25 μL/mL. In phase I clinical trial, no toxicological manifestations such as edema, erythema or eschar was observed, allowing the secure verification of the formulations in Phase II, which after 40 days of treatment there was mycological cure of 60% for the group treated with oil. All data collected demonstrate the use of essential oil of C. citratus, as another therapeutic option for treatment of pityriasis versicolor, but a randomized phase III to be developed to validate them.